Pengaruh Pembiayaan dalam Era Presiden Jokowi dan SBY pada Tahun 2010-2019 terhadap Pemerataan Peningkatan Pembangunan Jalan di Indonesia - Prasedyawati, Dhini Rizky; Soesilo, Nining Indroyono (Jurnal Kebijakan Ekonomi, 2022)
This study aims to find quantitative empirical evidence on the Effect of Financing in the Era of Presidents Jokowi and SBY from 2010 to 2019 on the Equitable Improvement of Road Construction in Indonesia. The analysis was carried out using panel data regression and common effect method, with the unit of observation being 11 provinces in Indonesia over a period of 10 years, during from 2010 to 2019. The dependent variable in this study is the length of the national road, while the independent variables are the APBN, Foreign Loans, Population, GRDP, the leadership dummy and the regional dummy. After doing the overall analysis, it can be seen that the length of the national road during the Jokowi administration had a positive and significant impact on the development of national roads in Indonesia. When viewed from the regional dummy, all of them have a positive and significant impact on several islands such as Sumatra, Java, Bali Nusa Tenggara, and Papua Maluku. This indicates that equitable development during the Jokowi administration is going well.